The OPIT system part I. - Packer, John C.; Brailsford, David F. (North-Holland, 1973)
The OPIT program is briefly described. OPIT is a basis-set-optimising, self-consistent field, molecular orbital program for calculating properties of closed-shell ground states of atoms and molecules. A file handling technique is then put forward which enables core storage to be used efficiently in large FORTRAN scientific applications programs. Hashing and list processing techniques, of the type frequently used in writing system software and computer operating systems, are here applied to the creation of data files (integral label and value lists etc.). Files consist of a chained series of blocks which may exist in core or on backing store or both. Efficient use of core store is achieved and the processes of file deletion, file re-writing and garbage collection of unused blocks can be easily arranged. The scheme is exemplified with reference to the OPIT program.